Archie giant comics collection - DeCarlo, Dan 1919-2001; Gladir, George 1925-2013; Parent, Dan; Ruiz, Fernando (Archie Comic Publications, 2015)
Presents short comic strips starring Archie, Betty, Veronica, Jughead, and their friends
"All stories previously published...in magazine form 1941-2015"--Title page verso
"Archie characters created by John L. Goldwater; the likeness of the original Archie characters were created by Bob Montana"--Title page verso
Keywords: Jugend; High school; Freundschaft; Comic